2017
DOI: 10.1109/tpel.2016.2583467
|View full text |Cite
|
Sign up to set email alerts
|

New Integrated Multilevel Converter for Switched Reluctance Motor Drives in Plug-in Hybrid Electric Vehicles With Flexible Energy Conversion

Abstract: This paper presents an integrated multilevel converter of switched reluctance motors (SRMs) fed by a modular front-end circuit for plug-in hybrid electric vehicle (PHEV) applications. Several operating modes can be achieved by changing the on-off states of the switches in the front-end circuit. In generator driving mode, the battery bank is employed to elevate the phase voltage for fast excitation and demagnetization. In battery driving mode, the converter is reconfigured as a four-level converter, and the cap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
50
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 127 publications
(52 citation statements)
references
References 51 publications
0
50
0
2
Order By: Relevance
“…Three-phase switched reluctance (SR) motor drives with integrated charging functions are proposed in [28,29]. Less active switches are adopted in [28], and a three-phase rectifier is used to connect with the internal combustion engine (ICE) generator and the grid.…”
Section: Comparison With Relevant Workmentioning
confidence: 99%
“…Three-phase switched reluctance (SR) motor drives with integrated charging functions are proposed in [28,29]. Less active switches are adopted in [28], and a three-phase rectifier is used to connect with the internal combustion engine (ICE) generator and the grid.…”
Section: Comparison With Relevant Workmentioning
confidence: 99%
“…In this paper, an SMIB system with losses is underscored, whose model is as follows: dδ/dt = ω N ω Mdω/dt = P − EUB 12 sin δ − EUG 12 cos δ − Dω (1) where δ denotes the rotor angle of the machine with respect to infinite bus; ω denotes the rotating speed of the machine; M denotes the inertia coefficient of the machine; D denotes the damping coefficient of the machine; U is the voltage of the infinite bus; P = P m − G 11 E 2 , where P m denotes the mechanical power, E is the voltage behind direct axis transient reactance, and G 12 (G 11 ) denotes the conductance of the element in the first row and second (first) column of the reduced admittance matrix; B 12 denotes the susceptance of the element in the first row and second column of the reduced admittance matrix; and ω N denotes the synchronous machine speed. The losses from the transmission systems and transfer conductances are expressed by EUG 12 cosδ.…”
Section: A Model Of Power System With Lossesmentioning
confidence: 99%
“…However, SCDs were considered small in power systems previously. Nowadays, renewable energy and electric vehicles have become integrated into to power systems [1][2][3]. Recently, it has been shown that wind power output is an intermittent energy resource [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Buck‐boost converters are single‐input single‐output (SISO) model and do not have any energy storage device. A switch reluctance motor drive integrated with a fast controller and a SISO converter are presented .…”
Section: Introductionmentioning
confidence: 99%
“…A switch reluctance motor drive integrated with a fast controller and a SISO converter are presented. 5,6 High-frequency galvanic isolation is achieved in the grid-connected inverter system through a transformer. 7 For the buck-boost converter 8 to operate with a wide voltage conversion range, it requires two more switches than the conventional buck-boost dc-dc converter.…”
mentioning
confidence: 99%